Ultrastructural Study of the Neuromuscular Junctions of Extensor Digitorum Longus Muscle (M. extensor digitorum longus) of the Mice - Boaro, Sueli N. [UNESP]; Fragoso Neto, Raul Antonio [UNESP] (Soc Chilena Anatomia, 2009)
The neuromuscular junction of the extensor digitorum longus muscle of fingers was analyzed in 21 young (three months) and old (from six to 25 months) mice, from both genders. Morphologic changes were found throughout the mouse life, being more frequent and visible with aging. According with the data described in the literature consulted and the observations taken in this research, it becomes clear that a continuous process of morphological remodeling occurs in all neuromuscular ultrastructural junctions of the extensor digitorum longus muscle of fingers, during the life of the animal. Theses changes are characterized by figures of myelin in the cytoplasm of Schwann cells, pleomorphic and multivesiclar bodies, mitochondrias with morphologically altered crests in the axon terminal and degenerated junction folders. Coated vesicles are common in older animals and rare in young animals.
Keywords: Neuromuscular junctions; Mice; Ultrastructure; Extensor digitorum longus muscle